IRON CONTENT, HARDNESS AND ACCEPTABILITY OF BISCUITS FROM COMPOSITE CASSAVA AND WHEAT FLOURS SUBSTITUTED WITH GREEN SPINACH FLOUR - Rusdin Rauf; Nurdiana Nurdiana; Dwi Sarbini (Universitas Muhammadiyah Surakarta, 2018)
The main cause of the high prevalence of iron deficiency anemia of children in Indonesia is the low intake of iron. Green spinach flour as a source of iron can be used as a substitution material in the manufacture of biscuits. The purpose of the study was to evaluate the effect of green spinach flour substitution on iron, hardness and acceptance levels of biscuits from composite cassava flour and wheat flour. The research was conducted by substituting the green spinach flour with various levels of 0%, 2.5%, 5% and 7.5%. The biscuits were then tested for the iron using Atomic Absorption Spectrophotometer (AAS), hardness using texture analyzer and acceptability. The results indicated that there was a substitution effect of green spinach flour to iron and acceptability of biscuits, whereas, there was no effect on the hardness. The higher the substitution of green spinach flour, the higher the iron level of the biscuit. The highest iron level was displayed by biscuit with the substitution of 7.5%, which was 89.82mg/kg. The hardness of biscuits was not affected by the substitution of green spinach flour. The range of biscuit hardness levels was between 2592.16g - 3985.83g. Biscuit with 5% substitution of green spinach flour gave the highest acceptability. The iron requirement of Indonesian school-age children (7-9 years) can be fulfilled by consuming biscuits (5% green spinach flour) as much as 14 grams or equivalent to 3 pieces of biscuit for a day.